Transformative retail services: Elevating loyalty through customer well-being. (November 2018) - Troebs, Cord-Christian; Wagner, Tillmann; Heidemann, F.
Abstract: Transformative retail services are an emerging business practice in the industry, designed to increase the well-being of customers and non-customers alike. Putting into practice the suggestion of the relevant literature to address additional firm-related outcomes beyond well-being, this research examines the impact of transformative retail services on customer well-being, which in turn is proposed to elevate loyalty intentions via the mediators experienced gratitude, reciprocity, and brand-related evaluations. The findings of one behavioral experiment and one field experiment are presented. While both transformative retail services offered for free as well as paid services increase customer well-being, only free transformative retail services positively affect customer loyalty intentions and its mediators.